1999
DOI: 10.2527/1999.7751048x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prepartum body condition score change on reproduction in multiparous beef cows calving in moderate body condition.

Abstract: Multiparous, spring-calving beef cows (n = 250) were used to determine whether large changes in body energy reserves during mid- to late gestation influenced subsequent reproductive performance of cows calving in moderate body condition. In three states, cows were blocked by BW and body condition score (BCS; 1 = emaciated to 9 = obese) then allotted to receive either a high or low plane of nutrition from late summer to early winter over a 3-yr period. This generated an array of BCS by the beginning of the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0
19

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 19 publications
7
36
0
19
Order By: Relevance
“…Vieira et al (2006) determined in primiparous Nelore cows, an average body weight of 436.0 kg at a date close to calving, during four years of observations. Morrison et al (1999), in a study with multiparous cows presenting moderate body condition score (3-3.5), observed that moderate loss of body reserves in the final third of gestation did not influence subsequent reproductive performance, if forage availability was not limiting to consumption post-calving. In the present experiment, cows grazing on natural pastures pre-calving lost an average of 0.31 points of body condition score until calving.…”
Section: Resultsmentioning
confidence: 99%
“…Vieira et al (2006) determined in primiparous Nelore cows, an average body weight of 436.0 kg at a date close to calving, during four years of observations. Morrison et al (1999), in a study with multiparous cows presenting moderate body condition score (3-3.5), observed that moderate loss of body reserves in the final third of gestation did not influence subsequent reproductive performance, if forage availability was not limiting to consumption post-calving. In the present experiment, cows grazing on natural pastures pre-calving lost an average of 0.31 points of body condition score until calving.…”
Section: Resultsmentioning
confidence: 99%
“…The maintenance of body energy reserves is considered to be the basis of any reproductive management strategy (Houghton et al 1990;Morrison et al 1999;Flores et al 2008). It is well known that the Gonadotropin releasing hormone (GnRH) pulse generator system and subsequent secretion of GnRH from the hypothalamus are inhibited by under nutrition.…”
Section: Managing Reproduction Within a Resource Limiting Environmentmentioning
confidence: 99%
“…A diferença de peso entre os dois grupos de vacas (Tabela 2) reduziu do acasalamento até o desmame, comprovando que as vacas em anestro profundo apresentaram ganho compensatório nesse período, promovendo equilíbrio no desempenho reprodutivo de ambos os grupos (Morrison et al,1999;Jaume & Moraes, 2002;Pimentel et al, 2005). Vacas em anestro superficial demonstraram tendência a desempenho reprodutivo melhor (Tabela 3), evidenciando que este grupo de vacas parece responder com maior eficiência ao protocolo de indução/sincronização de cio.…”
Section: Resultsunclassified
“…Os resultados obtidos confirmam que a produção de leite não influencia a condição reprodutiva nem a fertilidade pós-parto de vacas de corte com condição corporal moderada conforme observado por Pimentel et al (2005) e Brauner et al (2006. O equilíbrio entre as vacas de nível superior e inferior de produção de leite está relacionada ao fato de essas vacas apresentarem condição corporal moderada durante todo o período pós-parto, uma vez que a condição corporal é um fator marcante em relação ao desempenho produtivo e reprodutivo pós-parto em vacas (Spitzer et al, 1995;Morrison et al, 1999;Wettemann et al, 2003;Hess et al, 2005). A taxa de gestação não ocasionou diferença (P>0,05) nas variáveis de produção estudadas (Tabela 2).…”
Section: Resultsunclassified